FEATURES OF ADVERTISING DISCOURSE AND TEXT (European Journal of Interdisciplinary Research and Development, 2024)
Advertising discourse and text are unique forms of communication designed to persuade, inform, and engage audiences, usually with the goal of promoting products, services, or ideas. The features of advertising discourse and text reflect a blend of linguistic, psychological, and visual strategies aimed at capturing attention and influencing consumer behavior. The given article tries to discuss the essential key features.